Analysis of Factors Influencing the Sustainability of the Freshwater Fisheries Cultivation Center of the Sibolga Fisheries College - Sipahutar, Emerson Junior; Effendi, Ihsan (Amkop Management Accounting Review (AMAR), 2026)
This research endeavors to examine the determinants affecting the business sustainability of the Freshwater Fisheries Cultivation Center at the Sibolga Fisheries College, an institution crucial for enhancing community well-being and food security through the utilization of local resources. The variables under investigation encompass financial inclusion, risk management practices, mentoring initiatives, financial technology adoption, business partnerships, entrepreneurial competence, and entrepreneurial orientation, all in relation to business sustainability. Employing a quantitative methodology, this study utilizes an associative design. Data collection involved the distribution of questionnaires to both center managers and fisheries business stakeholders within Sibolga. Multiple regression analysis was employed to examine the data. The findings indicated that, when considered together, all seven independent variables exerted a positive and statistically significant influence on business sustainability. When assessed individually, financial inclusion, risk management, mentoring programs, and entrepreneurial competence demonstrated the most substantial contributions. Consequently, this study recommends enhancing access to formal financial resources, instituting structured risk management protocols, providing continuous mentoring support, improving digital literacy, and fostering cooperative-based partnerships to bolster the competitiveness of farmers.